2008
DOI: 10.1016/j.jtcvs.2007.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Robotic totally endoscopic coronary artery bypass: A word of caution implicated by a five-year follow-up

Abstract: Endoscopic surgery on the beating heart remains the ultimate goal for minimally invasive coronary artery surgery. The clinical outcomes and need for reintervention of the target vessel leave room for improvement and may be considered reflective of early experiences typically associated with dramatic departure from conventional therapy. Moving forward, advances in instrumentation and anastomotic technology seem to be essential for reproducible and reliable coronary anastomosis in a totally endoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…In a follow-up study of the Dresden experience, freedom from major adverse cardiac and cerebral events for the first 41 patients at 5 years was 75.6%. 43 We found a similar rate of major adverse events in our first 25 single-vessel AHTECAB patients, 26 but in this Innsbruck Medical University experience, we also noted a dramatic improvement of freedom from major adverse cardiac and cerebral events for the second, third, and fourth cohorts of 25 patients. Intramyocardial, heavily calcified, and very small target vessels in beating heart approaches Ascending aortic diameter Ͼ35 mm and significant aortoiliac atherosclerosis in on-pump arrested heart approaches CABG procedures were performed at the 2 institutions.…”
Section: Intermediate and Long-term Resultssupporting
confidence: 60%
“…In a follow-up study of the Dresden experience, freedom from major adverse cardiac and cerebral events for the first 41 patients at 5 years was 75.6%. 43 We found a similar rate of major adverse events in our first 25 single-vessel AHTECAB patients, 26 but in this Innsbruck Medical University experience, we also noted a dramatic improvement of freedom from major adverse cardiac and cerebral events for the second, third, and fourth cohorts of 25 patients. Intramyocardial, heavily calcified, and very small target vessels in beating heart approaches Ascending aortic diameter Ͼ35 mm and significant aortoiliac atherosclerosis in on-pump arrested heart approaches CABG procedures were performed at the 2 institutions.…”
Section: Intermediate and Long-term Resultssupporting
confidence: 60%
“…One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10). Eighteen additional studies reported on a mixture of different surgical techniques (18,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). A summary of the study selection process is presented in the PRISMA chart in Figure 1, and a summary of study characteristics is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies were excluded from the final analysis due to a mixed dataset for different surgical techniques (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) or use of cardiopulmonary bypass (36)(37)(38)(39)(40)(41), or use of an outdated robotic system other than the da Vinci system (18,34,35). Of the patients who were included for statistical analysis in the selected studies on off-pump TECAB, on-pump TECAB and robotic MIDCAB, the mean age ranged from 58 to 67, and 51-88% of patients were male.…”
Section: Resultsmentioning
confidence: 99%
“…One study even reports 100% survival at 41 months (9). In another paper showing 93% survival at 5 years, all deaths on followup were non-cardiac in nature (4). Figure 1 depicts the collective survival curve derived from the literature data.…”
Section: Methodsmentioning
confidence: 99%